二價銅離子化學偵測分子的合成及cell imaging的應用 - 吳淑褓; WU SHU-PAO (My University, 2011)
這個計畫主要是設計二價銅離子化學偵測分子，用以偵測二價銅離子。整個計畫分 為三部分，分別以pyrene，rhodamine 及奈米金粒子當成訊號來源，分別接上螯合基來 進行金屬離子的辨識。所設計的分子，分別測試其對於個別金屬離子的選擇性，所選用 金屬離子包括Ca(II), Cd(II), Co(II), Cu(II), Fe(II), Fe(III), Hg(II), Mg(II), Mn(II), Ni(II), Zn(II)。主要觀察金屬離子對化學偵測分子的鍵結，是否造成吸收波長或是螢光強度的 改變，產生辨識的效果。有關所設計化學偵測分子的評估，包括金屬離子的選擇性(以 UV-Vis 及螢光光譜判定)、二價銅離子的鍵結常數(binding affinity constants)、pH 對鍵 結的影響(pH dependent binding study)。所設計的二價銅離子化學偵測分子，測試後發現 屬於螢光OFF-ON 的偵測分子，將進行細胞實驗，來評估是否能夠在細胞中偵測銅離子。

The project is focused on the development of Cu(II) chemosensors. Three series of Cu(II) chemosensors based on pyrene, rhodamine and nano gold particles are designed for Cu(II) sensing. Metal ions such as Ca(II), Cd(II), Co(II), Cu(II), Fe(II), Fe(III), Hg(II), Mg(II), Mn(II), Ni(II), Zn(II) are going to test the selectivity of chemosensors. The detailed studies include metal ion selectivity studied by UV-Vis and fluorescence spectra, binding affinity constants and pH dependent binding study. Chemosensors which can detect Cu(II) as a fluorescent turn-on process are going to test their Cu(II) detecting ability in living cells.
Synthesis and Evaluation of Cu(Ii) Chemosensors for Cell Imaging